SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF THE MODERN STUDENT - Y. V. Kukanova (Образование и наука)
The paper reveals the findings of a sociological research, conducted in January 2013 and aimed at defining the modern student’s socio-psychological profile. The survey involved 415 students aged from 17 to 22, studying at Moscow State Regional University, Russian State University of Tourism and Services, and the Financial and Technological Academy. The questionnaire, entitled to reveal the social facts, affecting students’ activity and behavior, as well as the conscious phenomena (motives, values, attitudes, etc.), registered the students’ opinions on a wide range of both the social life and professional preference issues.The research presents the students’ socio-demographic characteristics, personal value orientations in different activity spheres, and cultural level; socialization problems and specifics of cooperation and interrelation with surrounding people being denoted along with participation in social and political life, and informal organizations.The main conclusion of the research emphasizes the fact of students’ exposure to the complicated socialization conditions. However, despite the adaptation problems, the author points out the growth of self-consciousness and intention to defend their opinions as the distinctive feature of that social group, the self-esteem being the primary behavior regulator.